Midterm conversations as co-creation of equitable and inclusive formative assessment - Lesnick, Alice; Evans, Sabea K.; Schall, Margo; Cook-Sather, Alison (International Journal for Students as Partners, 2024)
Although assessment of student learning remains a thorny area for co-creation in education, a growing number of researchers and practitioners advocate and enact partnership in formative and summative assessment as part of equity work. In this case study, we join these efforts in reflecting on students’ and our own experiences of the midterm conversation that we use as a key formative assessment structure and process across three co-facilitated courses. The midterm conversation—a partnership among students and instructors as co-teachers—is embedded in course design and curriculum with the goal of advancing, informing, and sustaining our pedagogical commitments. This case illustrates how we practice assessment as dialogue and as emergent understanding. This practice is based on an expectation of diverse learning goals and outcomes and on trust in students’ capacities to direct their learning with reference to their own interests and standards for their work.